Fulminant eye infection in a patient with nephrotic syndrome. Issue 7 (28th May 2018) - Koratala, Abhilash; Malpartida, Freddy R.; Ruchi, Rupam
Key Clinical Message: Endophthalmitis is a bacterial or fungal infection inside the eye, involving the vitreous and/or aqueous humors. High index of suspicion is required for this condition in immunocompromised patients with ocular complaints as it can worsen rapidly and lead to permanent loss of vision. Abstract : Endophthalmitis is a bacterial or fungal infection inside the eye, involving the vitreous and/or aqueous humors. High index of suspicion is required for this condition in immunocompromised patients with ocular complaints as it can worsen rapidly and lead to permanent loss of vision.